2021
DOI: 10.1093/qjmed/hcab100.110
|View full text |Cite
|
Sign up to set email alerts
|

Serum MicroRNA-222 Expression for Malignancy Prediction in Euthyroid Patients with Indeterminate Thyroid Nodule

Abstract: Background The Prevalence of thyroid nodules is rising nowadays, luckily most of them are benign. The risk of malignancy 5-15%, which necessitates the ultimate need to accurately distinguish benign from malignant nodule to avoid unnecessary thyroidectomy with risk of recurrent laryngeal nerve injury, postoperative hypothyroidism and lifetime thyroid replacement therapy, and other complications related to surgery and anaesthesia. Recent evidence suggests that circulating miRNA might have proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As shown in Figure 7, the sensitivity analysis confirmed that the random effects model was appropriate based on both the goodness of fit (Figure 7A) and bivariate normality (Figure 7B). Influence analysis revealed that Cantara et al [18], Li et al [30] , Zhang et al [32], Mohamed et al [25],and Censi et al [27] were the studies with the most significant impact on weight (Figure 7C).…”
Section: Sensitivity Analysesmentioning
confidence: 98%
“…As shown in Figure 7, the sensitivity analysis confirmed that the random effects model was appropriate based on both the goodness of fit (Figure 7A) and bivariate normality (Figure 7B). Influence analysis revealed that Cantara et al [18], Li et al [30] , Zhang et al [32], Mohamed et al [25],and Censi et al [27] were the studies with the most significant impact on weight (Figure 7C).…”
Section: Sensitivity Analysesmentioning
confidence: 98%